EFEKTIFITAS MEDIA FLIP FOLD DALAM MENINGKATKAN KERAPIAN MELIPAT PAKAIAN BAGI TUNANETRA X DI SLB A PAYAKUMBUH - Ari Fitra (Universitas Negeri Padang, 2014)
Abstrack: This research was aimed at testing the effectiveness of using Flip Fold media to improve the neatness of the student with visual impairment in folding the clothes in class IV of SLB A Payakumbuh. This research applied Single Subject Research approach and A-B-A design. The subject of the research was a student with visual impairment in class IV. To measure the research variables, percentage technique was applied. Based on the result of data analysis, it was found that the use of Flip Fold media is effective to improve the neatness of the student with visual impairment in folding the clothes in class IV of SLB A Payakumbuh.